ASSESSMENT OF POTATO TUBER RESISTANCE AGAINST DRY ROT - Stefańczyk, Emil (Plant Breeding and Seed Science, 2017)
Fungi of the genus Fusarium display inter- and intraspecific variation in their pathogenic capabilities. Although no resistance genes against dry rot have been identified, some indications of the possible defense responses are noticeable, since a single isolate might cause lesions of various sizes when infecting tubers of different potato cultivars. Pathogenicity tests are routinely used to assess potato tubers resistance against dry rot; a setup of pathogenicity test performed at Młochów Research Center is described in this work.